Analysis of Radiopaque Gastrointestinal Foreign Bodies Expelled by Spontaneous Passage in Children: A 15-Year Single-Center Study - Yeh, Hung-Yu; Chao, Hsun-Chin; Chen, Shih-Yen; Chen, Chien-Chang; Lai, Ming-Wei (Frontiers in Pediatrics, 2018)
Background: Most ingested foreign bodies (FBs) pass spontaneously through the gastrointestinal (GI) tract, but only limited data on transit time are available. We evaluated the relationship of FB size and shape with transit time. Methods: We retrospectively reviewed medical records collected over 15 years (January 2001 to December 2015) on pediatric patients with radiopaque FBs in the GI tract. We categorized the FBs as regularly (round or spherical) or irregularly shaped (ovoid, long, flake-like, or projecting) and measured their sizes radiographically. The diameter of regularly shaped FBs and the length of irregularly shaped FBs were correlated with transit time. Results: We enrolled 87 patients with single FBs in the GI tract for whom precise details of transit time were available; their mean age was 3.48 years. Of the 87 FBs, 61 (70.1%) were regularly shaped, and 26 (29.9%) irregularly shaped. The diameter of regularly shaped FBs was positively associated with transit time, as revealed by Student’s t-test; diameters >1.5 and >2 cm were significantly correlated with longer transit times (p = 0.0027 and 0.0016, respectively). A trend toward an increased transit time for long irregularly shaped FBs was also apparent; the p-values for lengths of 1.5, 2, and 2.5 cm were 0.4574, 0.0646, and 0.0513, respectively (Student’s t-test). Conclusion: Most ingested FBs pass spontaneously. Small FBs that have passed the duodenal curve should be managed conservatively via clinical observation and radiographic surveillance. Our results indicate that the larger an FB is, the longer the transit time will be.